2018
DOI: 10.1093/abm/kay077
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interdisciplinary Outpatient Specialty Palliative Care on Survival and Quality of Life in Adults With Advanced Cancer: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background In advanced cancer, patients want to know how their care options may affect survival and quality of life, but the impact of outpatient specialty palliative care on these outcomes in cancer is uncertain. Purpose To estimate the impact of outpatient specialty palliative care programs on survival and quality of life in adults with advanced cancer. Methods Following PRISMA guidelines, we conducted a systematic review and meta-analysis of randomized controlled trials comparing outpatient specialty pallia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 64 publications
3
60
0
3
Order By: Relevance
“…Integration of PC in LT patients seems to be considered essential by all parts [13, 15, 21, 22]. Transplant candidates not only benefit from being provided PC, since they suffer from a terminal condition with significant needs, but also require a complete and complex medical care even when their condition is very advanced [39]. Also, LT patients who are removed from the waiting list often experience withdrawal of specialty care, feelings of abandonment and likely imminent death [34], all of which must be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Integration of PC in LT patients seems to be considered essential by all parts [13, 15, 21, 22]. Transplant candidates not only benefit from being provided PC, since they suffer from a terminal condition with significant needs, but also require a complete and complex medical care even when their condition is very advanced [39]. Also, LT patients who are removed from the waiting list often experience withdrawal of specialty care, feelings of abandonment and likely imminent death [34], all of which must be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…However, a series of studies published starting in 2010 demonstrated that early palliative care improved survival by an average of 4.6 months in patients with advanced cancer 20‐22 . These and other studies showed that early palliative care also improved quality of life and reduced distress in both patients and caregivers 20,22‐24 . Findings were extended in a recent high‐visibility study demonstrating that clinic‐based symptom monitoring and management improved quality of life and extended survival by 5 months in patients with cancer who received chemotherapy, perhaps because they received chemotherapy for a longer time 25,26 .…”
Section: The Need For Pghd In Cancer Carementioning
confidence: 96%
“…As recently as 1999, PROs were framed in terms of understanding tradeoffs between quantity and quality of life 19 . However, a series of studies published starting in 2010 demonstrated that early palliative care improved survival by an average of 4.6 months in patients with advanced cancer 20‐22 . These and other studies showed that early palliative care also improved quality of life and reduced distress in both patients and caregivers 20,22‐24 .…”
Section: The Need For Pghd In Cancer Carementioning
confidence: 99%
“…Presumably, during the early phases of follow-up, palliative care has not yet provided a substantial "dose" to affect survival odds, and beyond 18 months, most patients succumb to their illness regardless of the care received. In contrast to the 2 previous meta-analyses, Hoerger et al 6 also conducted sensitivity analyses using Guyot et al's 11 method to develop composite Kaplan-Meier curves to assess survival differences across all the RCTs considered. From this statistical method, it was found that the median survival advantage of outpatient palliative oncology care was 4.56 months.…”
Section: Impact Of Palliative Oncology Care On Survivalmentioning
confidence: 99%
“…After considering the 4 meta-analyses on palliative oncology care, [4][5][6][7] the benefits for patient quality of life and survival are clear. Moving forward, disseminating these research findings will be critical to improve the lives of cancer patients and, more generally, public health.…”
Section: Disseminating Critical Findings Expanding Palliative Care Pmentioning
confidence: 99%